Optimising coagulation and ozone pre-treatments and comparing the efficacy of differently pre-treated grain distillery wastewaters in an upflow anaerobic sludge blanket (UASB) reactor - Robertson, Louise (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScFoodSc)--Stellenbosch University, 2014.